Applications and validations of the Minnesota density functionals - Zhao, Yan; Truhlar, Donald G. (Chemical physics letters, 2011)
[Display omitted] ► Reviewing recent applications and validations of the Minnesota density functionals (especially the M06 family). ► Emphasizing successes in nanochemistry, organic, inorganic, and biological chemistry, and catalysis. ► Highlighting the broad accuracy of the Minnesota functionals. We discuss and review selected recent applications and validations of the Minnesota density functionals, especially the M06 family, emphasizing nanochemistry, organic, inorganic, and biological chemistry, and catalysis and highlighting the broad accuracy of these functionals as compared to previous popular functionals for thermochemistry, kinetics, and noncovalent interactions.